The determinants of serum vitamin D levels in participants in a melanoma case–control study living in a temperate climate - Davies, John R. (Springer Netherlands, 2011)
BACKGROUND: We report the determinants of serum levels of vitamin D in a UK melanoma case–control study benefitting from detailed exposure and genotyping data. METHODS: Sun exposure, supplemental vitamin D, and SNPs reported to be associated with serum levels were assessed as predictors of a single serum 25-hydroxyvitamin D(3) measurement adjusted for season, age, sex, and body mass index. RESULTS: Adjusted analyses showed that vitamin D levels were sub-optimal especially in the sun-sensitive individuals (−2.61 nmol/L, p = 0.03) and for inheritance of a genetic variant in the GC gene coding for the vitamin D-binding protein (−5.79 for heterozygotes versus wild type, p = <0.0001). Higher levels were associated with sun exposure at the weekend in summer (+4.71 nmol/L per tertile, p = <0.0001), and on hot holidays (+4.17 nmol/L per tertile, p = <0.0001). In smoothed scatter plots, vitamin D levels of 60 nmol/L in the non-sun-sensitive individuals were achieved after an average 6 h/day summer weekend sun exposure but not in the sun-sensitive individuals. Users of supplements had levels on average 11.0 nmol/L higher, p = <0.0001, and achieved optimal levels irrespective of sun exposure. CONCLUSIONS: Sun exposure was associated with increased vitamin D levels, but levels more than 60 nmol/L were reached on average only in individuals reporting lengthy exposure (≥12 h/weekend). The sun-sensitive individuals did not achieve optimal levels without supplementation, which therefore should be considered for the majority of populations living in a temperate climate and melanoma patients in particular. Inherited variation in genes such as GC is a strong factor, and carriers of variant alleles may therefore require higher levels of supplementation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10552-011-9827-3) contains supplementary material, which is available to authorized users.